2014
DOI: 10.1016/j.freeradbiomed.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Designing inhibitors of cytochrome c/cardiolipin peroxidase complexes: mitochondria-targeted imidazole-substituted fatty acids

Abstract: Mitochondria have emerged as the major regulatory platform responsible for coordination of numerous metabolic reactions as well as cell death processes, whereby the execution of intrinsic apoptosis includes the production of reactive oxygen species fueling oxidation of cardiolipin (CL) catalyzed by cytochrome (cyt) c. As this oxidation occurs within the peroxidase complex of cyt c with CL, the latter represents a promising target for the discovery and design of drugs with anti-apoptotic mechanism of action. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 61 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…In this conformer, the pocket enclosing the heme group is solvent-exposed and large enough to accommodate the binding of a drug-like molecule. As previously noted (Jiang et al, 2014), this conformation naturally tends to close down (into the native compact conformer) unless stabilized by a bound ligand. The ligand-binding properties of this site and the conformational space accessible upon ligand binding were characterized by two sets of runs (Table 1).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…In this conformer, the pocket enclosing the heme group is solvent-exposed and large enough to accommodate the binding of a drug-like molecule. As previously noted (Jiang et al, 2014), this conformation naturally tends to close down (into the native compact conformer) unless stabilized by a bound ligand. The ligand-binding properties of this site and the conformational space accessible upon ligand binding were characterized by two sets of runs (Table 1).…”
Section: Resultsmentioning
confidence: 65%
“…Screening of the PM against libraries of small molecules as well as a database of known drug-target pairs led to seven hits (drug-like compounds), in addition to the identification of three repurposable drugs. Biochemical experiments to inhibit cyt c peroxidase activity confirmed that seven of these 10 newly discovered compounds/drugs exhibit efficiencies comparable to or better than those observed (Jiang et al, 2014) for TPP-n-ISA molecules, opening the way to new molecular intervention strategies for modulating mitochondrial-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Some of these therapies attempt to decrease the oxidative stress in the mitochondrial environment [203], while others focus on structural components of mitochondria [204208]. It can be argued that CR and inhibition of mTOR signaling can do both, and thus, these two interventions, described above, and may also be considered to be mitochondrial therapies.…”
Section: Mitochondrial Targeted Therapiesmentioning
confidence: 99%